Migration, citizenship, and repatriation: overseas Chinese in Malaya, 1900-1952 - Low, Choo Chin; Shi, Xiangkun (Penerbit UKM, 2025)
This paper examines the intersection between repatriation, immigration control, and citizenship policies in British Malaya. It seeks to understand how repatriation practices, immigration control, and citizenship legislation defined the distinctions between “citizens” and “aliens” among the Overseas Chinese in Malaya. The discussion is organised into three phases: the economic decline of the 1930s, the aftermath of World War II, and the Malayan Emergency. Repatriation was employed by the British colonial authorities to maintain law and order against undesirable alien Chinese individuals; however, it did not apply to British subjects and federal citizens. The Emergency (Immigration Ordinance) Regulations 1952 further exacerbated the distinction between citizens and aliens by limiting entry rights to British subjects and federal citizens. The State Nationality Enactment of 1952, with its delayed jus soli provisions, symbolised the automatic right of second-generation aliens to federal citizenship. Therefore, these citizens were granted the rights of entry and stay and were excluded from repatriation procedures. The findings suggest that repatriation practices, citizenship liberalisation, and immigration legislation have established the distinctions between “citizens” and “aliens,” thereby influencing the rights to stay and the entry rights of overseas Chinese.